2015
DOI: 10.1152/ajplung.00220.2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glutathione-S-transferase (GST) inhibition on lung epithelial cell injury: role of oxidative stress and metabolism

Abstract: Influence of glutathione-S-transferase (GST) inhibition on lung epithelial cell injury: role of oxidative stress and metabolism. Am J Physiol Lung Cell Mol Physiol 308: L1274 -L1285, 2015. First published April 10, 2015; doi:10.1152/ajplung.00220.2014.-Oxidant-mediated tissue injury is key to the pathogenesis of acute lung injury. Glutathione-S-transferases (GSTs) are important detoxifying enzymes that catalyze the conjugation of glutathione with toxic oxidant compounds and are associated with acute and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Looking at detoxification enzymes of the glutathione family, GSTP1 is a phase 2 enzyme involved in xenobiotic metabolism, antioxidant defense and maintenance of the cellular redox hemostasis [25,26]. GSTP1 catalyzes the conjugation of hydrophobic and electrophilic compounds with reduced glutathione [26] and loss of this enzyme has been associated with nuclear oxidative stress damage and potentiation of cell injury by ROS such as those released by TS [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at detoxification enzymes of the glutathione family, GSTP1 is a phase 2 enzyme involved in xenobiotic metabolism, antioxidant defense and maintenance of the cellular redox hemostasis [25,26]. GSTP1 catalyzes the conjugation of hydrophobic and electrophilic compounds with reduced glutathione [26] and loss of this enzyme has been associated with nuclear oxidative stress damage and potentiation of cell injury by ROS such as those released by TS [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…We found that these nonlinearly expressed genes selected by NDC ( Figure 7E) were enriched in the ten terms, and these terms have no overlap between other terms enriched by reference methods. However, for the glutathione conjugation term, Fletcher et al (2015) reported that glutathione-S-transferases (GSTs) catalyze the conjugation of glutathione with toxic oxidant compounds and were associated with acute and chronic inflammatory lung diseases. For the glycerophospholipid metabolism term, phosphoenolpyruvate carboxykinase (PEPCK) has been shown to promote cancer cell survival under conditions of nutrient deprivation, a typical feature in solid cancers, as well as cancer growth (Méndez-Lucas et al, 2014;Leithner et al, 2015;Montal et al, 2015;Vincent et al, 2015).…”
Section: Enrichment Analysis Of Pathways and Biological Processesmentioning
confidence: 99%
“…We would expect a slower aging process because of partial de-repression of the HH pathway in Hhip +/− mice (22), whereas we observed accelerated aging-associated emphysema and increased cellular senescence in Hhip +/− mice. By searching for additional interacting proteins of HHIP, we identified GSTP1, a detoxification gene, which protects murine lung epithelial cells from H 2 O 2 -induced cell death (38). Therefore, the interaction between HHIP and GSTP1 in the cellular mitochondrial fraction suggests that HHIP may reduce oxidative stress by binding to and possibly increasing the activity of GSTP1.…”
Section: Hhip Interacts With Gstp1 and Enhances Glutathione-conjugatingmentioning
confidence: 99%